STYLE FEATURES OF GOTHIC STYLE IN MODERN LEVEL DESIGN - Зеленська, Вероніка; Тюрікова, Олена (SWorldJournal, 2025)
This article examines the uses of the Gothic style in level design. Today, the Gothic style is not only a focus of architectural and historical heritage, but also a part of pop culture due to its unique aesthetics. With the development of technology, art